Principles of projecting preschool education institutions - Usmankulov F.A; Aminova Rukhshona (International Journal on Orange Technologies, 2021)
This article describes the principles of projecting of preschool facilities, sanatorium-type kindergartens in the village, the scope of services for kindergartens located in rural areas, the development of plans (analytical schemes) depending on their type